Perancangan Sistem Monitoring Operasional Alat Berat di Pertambangan PT. Pamapersada Nusantara Berbasis Android - Taufiq, Aldi Muhammad; Hertina, Siti; Gunawan, Hendra (Sistemasi: Jurnal Sistem Informasi, 2025)
PT Pamapersada Nusantara (PAMA), a company operating in the mining sector, faces challenges in monitoring the performance of heavy equipment, which is still conducted manually. This method is prone to recording errors and disrupts the smooth flow of production processes. The issues include inaccurate logging of activities for Shovel and Haul Truck units, discrepancies in operator status during production, and the lack of real-time operational location information. This study aims to improve efficiency in identifying the status of heavy equipment—such as standby, delay, and down—through direct reporting by operators. The development methodology employed is Agile Scrum, with the work process divided into sprints to allow for continuous evaluation and refinement based on user needs. The outcome of this study is an Android-based application called MineTrack, which enables real-time monitoring of heavy equipment operations by utilizing GPS technology for location tracking and SQLite for data management. In conclusion, MineTrack enhances the accuracy of operational monitoring, supports more effective decision-making in heavy equipment management within the mining industry, and contributes to increased productivity while reducing the risk of operational errors.